Sedation protocols in non-traumatic SAH (SPRINT-SAH): A cross-sectional survey among German-speaking neurointensivists - Schmidbauer, Moritz L.; Lanz, Hugo; Maskos, Andreas; Putz, Timon; Kunst, Stefan; Dimitriadis, Konstantinos (Frontiers in Neurology, 2023)
Background In subarachnoid hemorrhage (SAH), titrating sedation to find a balance between wakefulness with the ability to perform valid clinical examinations on the one hand, and deep sedation to minimize secondary brain damage, on the other hand, is challenging. However, data on this topic are scarce, and current guidelines do not provide recommendations for sedation protocols in SAH. Methods We designed a web-based, cross-sectional survey for German-speaking neurointensivists to map current standards for the indication and monitoring of sedation, duration of prolonged sedation, and biomarkers for the withdrawal of sedation. Results Overall, 17.4% (37/213) of neurointensivists answered the questionnaire. Most of the participants were neurologists (54.1%, 20/37) and exhibited a long-standing experience in intensive care medicine (14.9 years, SD 8.3). Among indications for prolonged sedation in SAH, the control of intracranial pressure (ICP) (94.6%) and status epilepticus (91.9%) were most significant. With regard to further complications in the course of the disease, therapy refractory ICP (45.9%, 17/37) and radiographic surrogates of elevated ICP, such as parenchymal swelling (35.1%, 13/37), were the most relevant topics for experts. Regular awakening trials were performed by 62.2% of neurointensivists (23/37). All participants used clinical examination for the therapeutic monitoring of sedation depth. A total of 83.8% of neurointensivists (31/37) used methods based on electroencephalography. As a mean duration of sedation before attempting an awakening trial in patients with unfavorable biomarkers, neurointensivists suggested 4.5 days (SD 1.8) for good-grade SAH and 5.6 days (SD 2.8) for poor-grade SAH, respectively. Many experts performed cranial imaging before the definite withdrawal of sedation [84.6% (22/26)], and 63.6% (14/22) of the participants required an absence of herniation, space-occupying lesions, or global cerebral edema. The values of ICP tolerated for definite withdrawal were smaller compared to that of awakening trials (17.3 mmHg vs. 22.1 mmHg), and patients were required to stay below the threshold value for several hours (21.3 h, SD 10.7). Conclusion Despite the paucity of clear recommendations for sedation management in SAH in the pre-existing literature, we found some level of agreement indicating clinical efficacy for certain clinical practices. By mapping the current standard, this survey may help to identify controversial aspects in the clinical care of SAH and thereby streamline future research.